Peningkatan Proses Bisnis PT. Sambada Gatya Praya Dengan Metode Model-Based and Integrated Process Improvement (MIPI) - Iqbal, Muhamad; Jahroh, Siti; Djohar, Setiadi (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The global market developments is very fast that make a business need to adapt to keep competing. Business process was a vital component on the business if the business want to keep competing and developing. Business process must be keep developing with the proper and suitable methods. This study aims to analyze process improvement on PT. Sambada with Model-Based and Integrated Process Improvement method (MIPI). MIPI methods have 7 step, there are understand the business needs, understand the process, model and analyze process, redesign process, implement new process, asses new process, and review new process. The method was done until the fourth step, which is the redesign process step. On the first step, scanning was performed on the current condition of the company. The current condition of the company is depicted by the vision and mission of the company, the organization structure, market share, and complaints or mistakes data from consumers. On the second step, all current business process of the company is modeled. On the third step, all process were validated with all of the person in charge with the process. After that, the process is analyzed by value added analysis tool. Last, prosess improvement team was assembled to take charge with redesigned the new process which already improved. Pareto and Fishbone diagram were used to analyze and determined the focus of the problem being solved. The result of the study gives a new process that already fixed by applying the result from the analysis in accordance to MIPI method. Keywords: business process, fishbone, improvement, pareto, MIPI